VD_FINDINFO Décision / 2015 / 26 vom 29. Dezember 2014 - VD Tribunal cantonal (2014)
CLASSEMENT DE LA PROCÉDURE, VIOLATION D'UNE OBLIGATION D'ENTRETIEN | 217 CP, 319 CPP (CH), 393 al. 1 let. a CPP (CH)